Inclusão na diversidade: um desafio para os educadores - Santos Silva, Rita de Cácia; Santos Silva, Greice Fabiane (Revista Entreideias: educação, cultura e sociedade, 2006)
No intuito de contribuir com uma reflexão acerca do tema Inclusão na Diversidade, faremos uma abordagem sobre a prática escolar e o papel do professor na busca de uma educação de qualidade para todos. A análise aponta algumas das necessidades de formação do educador para atuar nessa nova perspectiva e sugere algumas transformações necessárias para o atendimento a essa diversidade, em compromisso com a mudança no quadro atual da educação. Palavras-chave: Diversidade; Educação especial; Inclusão. Abstract: In the aim of contributing with a reflection about the theme of Inclunding in the Diversity, we present an approach about the formation of teachers for the inclusive teaching presenting some suggestions in order to face the defeat of working with the student’s individual differences. This is a bibliographical study which analysis points the needs of a teacher’s formation that enables him/her to act in this new perspective and to the necessary changes to respond to this diversity of life forms with the compromise to change the present education portrait. Key words: Diversity; Special education; Inclusion.